2019
DOI: 10.3390/pharmacy7030128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pharmacy-Led Transition of Care Service on Post-Discharge Medication Adherence

Abstract: This study assesses the effectiveness of a pharmacy-led transition of care (TOC) service on increasing patients’ understanding of, and reported adherence to, medication post hospital discharge. A cross-sectional survey was administered to patients who were discharged from the hospital with at least one medication received via bedside delivery from the TOC service. Adherence was assessed by asking the patient if they had taken their discharge medications as instructed by the prescriber. Satisfaction with the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…However, clinicians working closely with CDC have reported that rehospitalized EVALI patients have at times not adhered to prescribed corticosteroid tapers (Lung Injury Response Clinical Working Group, personal communication, December 2019). Patient adherence to prescribed medications has been determined to be enhanced by inpatient pharmacist counseling before patient discharge (19,20) and that such counseling decreases rehospitalization. Thus, part of EVALI patient discharge planning should include inpatient pharmacist counseling, particularly for patients on a corticosteroid taper.…”
Section: Updated Guidance: Discharge Planningmentioning
confidence: 99%
“…However, clinicians working closely with CDC have reported that rehospitalized EVALI patients have at times not adhered to prescribed corticosteroid tapers (Lung Injury Response Clinical Working Group, personal communication, December 2019). Patient adherence to prescribed medications has been determined to be enhanced by inpatient pharmacist counseling before patient discharge (19,20) and that such counseling decreases rehospitalization. Thus, part of EVALI patient discharge planning should include inpatient pharmacist counseling, particularly for patients on a corticosteroid taper.…”
Section: Updated Guidance: Discharge Planningmentioning
confidence: 99%
“…The PSQSP survey results clearly showed patient satisfaction with the pharmacy services resulting in a mean score of 3.94 out of 4. Both high recall rate and satisfaction with care may boost patient’s adherence to their medications ( Gu et al, 2008 , Stroud et al, 2019 ). Furthermore, Stroud et al demonstrated the importance of follow up phone call on improving patient adherence in pharmacist-led TOC program ( Stroud 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different models exist for integrating pharmacist service into TOC programs ( Rochester-Eyeguokan 2016 ). A typical model involves the pharmacist conducting medication reconciliation, delivering patient-centered education, and resolving medication access issues during care transitions ( Stroud 2019 ). Such a model also involved pharmacist performing follow-up services to ensure patients adherence to their medication regimens without adverse outcomes upon returning to their homes.…”
Section: Introductionmentioning
confidence: 99%
“…A study done in 2019 found that when patients were educated properly on opioid use, patients took opioids for fewer postoperative days (Farley et al, 2019). One article found that when contacting patients after discharge, many of the patients still had questions about their medication and instructions (Stroud, Adunlin, & Skelley, 2019). The study identified 32% of patients still had questions even when counseled in the hospital, the results stress the importance of implementing a post-discharge follow-up phone call addressing questions and concerns the patient may have (Stroud, Adunlin, & Skelley, 2019).…”
Section: Proposed Evidence-based Solutionsmentioning
confidence: 99%
“…One article found that when contacting patients after discharge, many of the patients still had questions about their medication and instructions (Stroud, Adunlin, & Skelley, 2019). The study identified 32% of patients still had questions even when counseled in the hospital, the results stress the importance of implementing a post-discharge follow-up phone call addressing questions and concerns the patient may have (Stroud, Adunlin, & Skelley, 2019). The 5 A's Behavior Change Model is a patient centered counseling tool to encourage certain behavioral habits (Welzel et al, 2018).…”
Section: Proposed Evidence-based Solutionsmentioning
confidence: 99%